Letting things speak: a case study in the reconfiguring of a South African institutional object collection - Bloch, Joanne (Michaelis School of Fine Art, 2016)
In this thesis I examine the University of Cape Town (UCT) Manuscripts and Archives Department object collection, providing insights into the origins of the collection and its status within the archive. Central to the project was my application of a set of creative and affective strategies as a response to the collection, that culminated in a body of artwork entitled Slantways, shown at the Centre for African Studies (CAS) Gallery at UCT in 2014.The collection of about 200 slightly shabby, mismatched artefacts was assembled by R.F.M. Immelman, University Librarian from 1940 until 1970, who welcomed donations of any material he felt would be of value to future scholars. Since subsequent custodians have accorded these things, with their taint of South Africa's colonial past, rather less status, for many years they held an anomalous position within the archive, devalued and marginalised, yet still well-cared for. The thesis explores the ways in which an interlinked series of oblique or slantways conceptual and methodological strategies can unsettle conventional understandings of these archival things, the history with which they are associated, and the archive that houses them. I show how such an unsettling facilitates a complex and subtle range of understandings of the artefacts themselves, and reveals the constructed and contingent nature of the archive, as well as its biases, lacunae and limitations in ways that conventional approaches focusing on its evidentiary function allow to remain hidden. This set of slantways strategies includes the use of a cross-medial creative approach, and my focus on an a-typical, marginalised and taxonomy-free collection. Also important is the incorporation of my visual impairment as avital influence on my artwork, leading to an emphasis both on unusual forms of seeing and on the senses of smell, touch and hearing. Furthermore, my choice to follow a resolutely thing-centred approach led me to engage very closely with the artefacts' materiality, and subsequently with their actancy as archival things, which in turn influenced my conceptual and creative choices.